Child injury: Does home matter?. (March 2016) - Osborne, Jodie M.; Davey, Tamzyn M.; Spinks, Anneliese B.; McClure, Roderick J.; Sipe, Neil; Cameron, Cate M.
Abstract: This study examined the relationship between home risk and hospital treated injury in Australian children up to five years old. Women with children between two and four years of age enrolled in the Environments for Healthy Living (EFHL): Griffith Birth Cohort Study were invited to complete a Home Injury Prevention Survey from March 2013 to June 2014. A total home risk score (HRS) was calculated and linked to the child's injury related state-wide hospital emergency and admissions data and EFHL baseline demographic surveys. Data from 562 households relating to 566 child participants were included. We found an inverse relationship between home risk and child injury, with children living in homes with the least injury risk (based on the absence of hazardous structural features of the home and safe practices reported) having 1.90 times the injury rate of children living in high risk homes (95% CI 1.15–3.14). Whilst this appears counter-intuitive, families in the lowest risk homes were more likely to be socio-economically disadvantaged than families in the highest risk homes (more sole parents, lower maternal education levels, younger maternal age and lower income). After adjusting for demographic and socio-economic factors, the relationship between home risk and injury was no longer significant (p > 0.05). Our findings suggest that children in socio-economically deprived families have higher rates of injury, despite living in a physical environment that contains substantially fewer injury risks than their less deprived counterparts. Although measures to reduce child injury risk through the modification of the physical environment remain an important part of the injury prevention approach, our study findings support continued efforts to implement societal-wide, long term policy and practice changes to address the socioeconomic differentials in child health outcomes. Highlights: Disadvantaged children had higher injury rates despite living in lower risk homes. Socio-economic factors are important in predicting child injury. Continued effort required to address socioeconomic differentials in child health. Requires ongoing societal-wide, long term policy and practice changes.